A Systematic Literature Review of the Impact of Carbon Accounting Implementation on Sustainability - Yoewono, Harsono; Roziq, Mohammad (Dinasti Publisher, 2025)
This study presents a systematic literature review examining the impact of carbon accounting implementation on sustainability within the context of sustainable finance. Employing the PRISMA methodology, 72 articles were identified from the Scopus and Google Scholar databases, with the 9 most relevant studies selected for further descriptive and thematic analysis. The findings indicate that carbon accounting implementation positively influences corporate sustainability by contributing to emissions reduction, enhancing transparency, and strengthening corporate reputation. However, several studies also highlight inconsistencies between carbon accounting practices and the intended sustainability objectives. This review underscores the critical importance of integrating carbon accounting into corporate reporting systems and business strategies to support the achievement of environmental and social goals. The findings also suggest promising avenues for future research, particularly concerning the role of regulatory frameworks, industry-specific contexts, and implementation challenges in developing countries.